Active inflammatory biomarkers in oral lichen planus. (December 2015) - Santarelli, Andrea; Mascitti, Marco; Rubini, Corrado; Bambini, Fabrizio; Zizzi, Antonio; Offidani, Annamaria; Ganzetti, Giulia; Laino, Luigi; Cicciù, Marco; Muzio, Lorenzo Lo
Oral lichen planus (OLP) is a chronic disease, with a central role to cell-mediated autoimmunity. Osteopontin promotes migration and recruitment of immune cells, CD44 is its receptor, and Survivin seems to be important in skin/mucosa homeostasis. The aim of this study was to investigate their expression in biopsy specimens of patients with different OLP clinical types and healthy controls. Biopsy specimens from 30 patients with OLP (15 atrophic and 15 hyperplastic) and 15 healthy controls were subjected to immune-histochemical analysis, to detect the expression of osteopontin, CD44, and Survivin in oral epithelia. The distributions of positively stained cells were evaluated with a quantitative method, while the inflammation degree was evaluated with a semi-quantitative one. Expression of osteopontin and CD44 was higher in OLP than controls, while Survivin expression was lower in OLP patients. There was a greater reduction of Survivin expression in atrophic OLP than hyperplastic OLP. A correlation between osteopontin expression and a high degree of inflammation was found. Furthermore, Survivin expression was higher in cases with low intensity of inflammation. Osteopontin, CD44, and Survivin seem to be involved in OLP pathogenesis, and further investigations are needed for clarifying their role in this oral disease.